Distance-dependent homeostatic synaptic scaling mediated by A-type potassium channels - Ito, Hiroshi T.; Schuman, Erin M. (Frontiers in Cellular Neuroscience, 2009)
Many lines of evidence suggest that the efficacy of synapses on CA1 pyramidal neuron dendrites increases as a function of distance from the cell body. The strength of an individual synapse is also dynamically modulated by activity-dependent synaptic plasticity, which raises the question as to how a neuron can reconcile individual synaptic changes with the maintenance of the proximal-to-distal gradient of synaptic strength along the dendrites. As the density of A-type potassium channels exhibits a similar gradient from proximal (low)-to-distal (high) dendrites, the A-current may play a role in coordinating local synaptic changes with the global synaptic strength gradient. Here we describe a form of homeostatic plasticity elicited by conventional activity blockade (with TTX) coupled with a block of the A-type potassium channel. Following A-type potassium channel inhibition for 12 hrs, recordings from CA1 somata revealed a significantly higher miniature excitatory postsynaptic current (mEPSC) frequency, whereas in dendritic recordings, there was no change in mEPSC frequency. Consistent with mEPSC recordings, we observed a significant increase in AMPA receptor density in stratum pyramidale but not stratum radiatum. Based on these data, we propose that the differential distribution of A-type potassium channels along the apical dendrites may create a proximal-to-distal membrane potential gradient. This gradient may regulate AMPA receptor distribution along the same axis. Taken together, our results indicate that A-type potassium channels play an important role in controlling synaptic strength along the dendrites, which may help to maintain the computational capacity of the neuron.